ANALISIS PENERAPAN APLIKASI SISTEM AKUNTANSI PERSEDIAAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA DISTRIK NAVIGASI KELAS III PONTIANAK - Slamet Sogiarto; Rusmanto Lianto (SISFOTENIKA, 2011)
Abstracts : This paper was conducted to determine the factors influencing acceptance Accounting Inventory System applications approach using technology acceptance model (TAM) method. The factors such as Perceived usefulness, Perceived Ease of Use, Attitude Towards Behavior, Behavorial Intention to Use, Actual Technology Use and Demographic Factors. Dependent variable is the adoption application Inventory Accounting System, while the independent variables are Perceived usefulness (PU), Perceived Ease of Use (PEOU), Attitude Towards Behavior (ATU), Behavorial Intention to Use (BIU), Actual Technology Use (ATU), Demographic Factors (DFC). Analysis tool used is the Confirmatory Factors Analysis and Correlation Kendall Tau. Software used to help the writer to process the data is SPSS version 17 and AMOS. The conclusion of this research is the application of Accounting Inventory System application on Distrik Navigasi Divisi III Pontianak is now well received by employees who apply them, both individually and in groups. The advice can be given that it is better if not only on the stock and financial management using information technology, but all parts are there in the office, so that employee performance can be further increased. Keywords : Technology Acceptance Model, Confirmatory Factors Analysis, Kendall Tau Correlation, AMOS